11 Do cardiac rehabilitation services support those diagnosed with spontaneous coronary artery dissection (SCAD)?. (21st November 2022) - Gardiner, Nikki; Rockell, Karen; Adlam, David; Singh, Sally
Abstract : Background: Cardiac Rehabilitation (CR) is an intervention offered to patients predominately diagnosed with heart disease. However, over the last five years there are a growing number of people being diagnosed with SCAD. SCAD is a nonatherosclerotic aetiology of acute myocardial infarction; when a tear or a bruise develops in a coronary artery resulting in a blockage that prevents normal blood flow. The uptake and offer of CR to SCAD patients across the United Kingdom (UK) is currently not captured by the National Audit of Cardiac Rehabilitation. Aim: The Beat SCAD Charity ® were keen to explore the views of patients following their SCAD diagnosis, experiences of Cardiac Rehabilitation (CR) follow up and healthcare professionals knowledge of the condition. Methods: A survey was developed and advertised by the Beat SCAD charity® via their newsletter and closed Facebook group. Results: The sample size was N= 242 patients (96% female, average age 40 years), treatment received: 74% medical management. 86% were recommended to attend a CR programme. 57% reported starting a CR programme 6 weeks post event. Although 69% stated they completed a CR programme, only 40% attended an exercise programme and a subsequent 20% completed a discharge assessment. According to SCAD patients only 39% of CR professionals had perceived knowledge of SCAD. 67% patients were 'very likely' to recommend CR to their peers. Conclusion: CR HCPs are ideally placed to support those diagnosed with SCAD but improvements need to be made to increase the knowledge and rehabilitation needs for this bespoke population.